Chemical Composition of Paints and Primers as an Important Aspect of the Attribution of Late Russian Icons from the Urals Region - Kadikova, Irina F.; Lavrentyeva , Elena V. (Actual Problems of Theory and History of Art, 2023)
The article presents the results of the chemical analysis of the paint layer and primer of the Old Believer icons of the 18th century from the Urals (Nevyansk icon painting) and describes the changes in the composition of the artists’ palette during that century. An important part of the work was the study of more than twenty dated icons from the largest Ural collections. It was revealed that the icons of the first half of the 18th century were characterized by the following set of pigments: ochre of various shades, vermilion, red organic pigment, red lead, lead white, glauconite, synthetic azurite, copper resinate, natural indigo, less often — smalt. In the icons of the second half of the century the set of pigments changes: 1. glauconite and indigo are no longer used; 2. Prussian blue becomes an integral part of the artistic palette; 3. orpiment is widely used, both in its pure form and in mixed paints; 4. а number of minerals (natural malachite, crocoite, realgar), which are extremely rare in other centers of late Russian icon-painting, appear in the use of Nevyansk icon painters. Since malachite and crocoite are local minerals, their identification in the late Russian icons allows us to clarify the attribution and often indicates the Uralic origin of the items. In addition, our research has shown, that in the Nevyansk icon painting of the 18th century calcium sulfate was used as a primer, in most cases in the form of anhydrite.
Keywords: attribution and expertise of painting; Old Believer icons of the Urals; Nevyansk icons; Late Russian icon painting; technological analysis; pigments of icon painting; realgar; crocoite; malachite; anhydrite